If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-20-4x=-36-8x
We move all terms to the left:
-20-4x-(-36-8x)=0
We add all the numbers together, and all the variables
-4x-(-8x-36)-20=0
We get rid of parentheses
-4x+8x+36-20=0
We add all the numbers together, and all the variables
4x+16=0
We move all terms containing x to the left, all other terms to the right
4x=-16
x=-16/4
x=-4
| X+5/2=6/x | | 3p+3=12 | | 3x-1=11-3x | | 8=-5p-3 | | x+x=148° | | 400-3a=112 | | -20=-0.5k | | 12x+36=360 | | 3x-11=68 | | 120+8x=360 | | 8+4-3x2=10 | | 4-(2x+4)=-12 | | j-45/4=7 | | 2x^2+x^2=25^2 | | 90+6x+4+32=180 | | 2(b+5)+2=18 | | 13x-1=11x-7 | | 18+5h=48 | | 4|2x-2|+10=34 | | -6=-3(r+16) | | 2(0,5x+2)=39x-72 | | |3x-14|=4x | | 6=9m+12m | | -9m+12m=6 | | 9x-1=6-15x | | 2x^2-(3x-1)=0 | | -3(h+4)=6 | | 4-3x=5-6x7 | | 11=3(z-8)-7 | | 4(2x+3)=6x+6 | | 5=+6(3h+4) | | 88-s=8 |